WELLNESS TOURISM IN UBUD. “A QUALITATIVE APPROACH TO STUDY THE ASPECTS OF WELLNESS TOURISM DEVELOPMENT” - Meikassandra, Prilicia; Prabawa, I Wayan Sukma Winarya; Mertha, I Wayan (Journal of Business on Hospitality and Tourism, 2020)
This study aims to describe the aspects of wellness tourism development in Ubud. Adopted from Corbin theory (2006)  which states the body, mind and spirit as part of the five dimensions of wellness, namely physical wellness, emotional wellness, social wellness, intellectual wellness, and spiritual wellness, authors would therefore to identify product wellness, wellness activities, wellness dimension and life cycle of development of wellness tourism in Ubud. This study uses qualitative research methods, starting with literature studies related research about wellness tourism and in-depth interviews with wellness service providers in Ubud. In this study, the authors reviewed the literatures and analyzed the information collected from eight wellness service providers. The eight informants are determined by considering the type of wellness service scale such as spa resorts, health resorts, retreat centers, and wellness centers, located in Ubud. The results showed that wellness tourism in Ubud had fulfilled aspects and dimensions of wellness. This is reflected from the identification which was resulted where the highest-demanded wellness products in Ubud, namely yoga retreats, meditation retreats, spiritual retreats, detoxes and spa resorts. While wellness activities in Ubud are considered more relevant to Balinese-Hinduism lifestyles such as customs, cultural-religion activities and valuable-local knowledge of Balinese herbs in which are part of the wellness experience offered in Ubud. While in the terms of phase of development, the current situation of wellness tourism stays in development phase.